2008
DOI: 10.1680/geot.2008.58.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Compaction behaviour of clay

Abstract: This paper presents an experimental study of the compaction behaviour of non-active clay. One-dimensional static compaction tests were carried out at high and medium water content with matric suction monitoring using Trento high-capacity tensiometers. At lower water contents, a transistor psychrometer was used to measure post-compaction suction. Samples were compacted on the dry side of optimum to cover a wide range of compaction water contents and vertical stresses. Three water content regions were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 29 publications
15
102
1
5
Order By: Relevance
“…After moving across the LOO, suction contours at the wet side of the LOO head toward the origin of the e -e w plane. This result is in accordance with the observation in Kodikara's [1] analysis using the data reported by Tarantino and De Col [8] and some others. It is noted here that the suction value at the dry side of the LOO is dependent on the values of suction (S r ) and moisture contents (e wr ) at the residual conditions (at point H in Fig.…”
Section: Soil Suction At the Dry Side Of The Loosupporting
confidence: 93%
See 2 more Smart Citations
“…After moving across the LOO, suction contours at the wet side of the LOO head toward the origin of the e -e w plane. This result is in accordance with the observation in Kodikara's [1] analysis using the data reported by Tarantino and De Col [8] and some others. It is noted here that the suction value at the dry side of the LOO is dependent on the values of suction (S r ) and moisture contents (e wr ) at the residual conditions (at point H in Fig.…”
Section: Soil Suction At the Dry Side Of The Loosupporting
confidence: 93%
“…At each value of moisture content six duplicated soil samples were compressed by a given vertical stress (100, 200, 300, 600, 1200 or 1800 kPa) at loading rates varying from 20 to 50 kPa/min (higher rate for larger value of compression) for the sample at the dry side of optimum. As highlighted by Tarantino and De Col [8] that at a loading rate of 5 kPa/min matric suction in soil sample did not exhibit discontinuities, in this study the loading rate was slowed down to 5 kPa per min when the state path close to the LOO (when S r > 80%). This treatment is necessary to make sure water can run out of soil samples during drained path and air pressure will not build up in samples.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…Lambe and Whitman, 1969;Mitchell et al, 1965) the engineering properties of compacted cohesive soils were related to the compaction state, which was explained by the dispersed microstructure of soil compacted on the wet side and flocculated microstructure of the soil compacted on the dry side of the Proctor compaction curve. Mercury intrusion porosimetry tests for cohesive soils confirmed that the microstructure on the dry side of optimum water content was composed of aggregates with a welldefined distinction between the 'intra-aggregate pore population' and the 'inter-aggregate pore population' full of air, because water was located only in the aggregates (Delage et al, 1996;Tarantino and De Col, 2008). For material compacted on the wet side of the Proctor optimum water content, the initial bimodal pore size distribution depends heavily on the state of saturation during compaction (Delage et al, 1996).…”
Section: Introductionmentioning
confidence: 89%
“…14, which collates data reported by Romero et al (2011) on statically compacted Boom clay. Tarantino & de Col (2008) published MIP data on a few statically compacted samples of kaolin. The calculation of î m has also been based on the intrusion-extrusion diagram of MIP tests (Fig.…”
Section: Mapping Microstructure On the Compaction Planementioning
confidence: 99%